Introduction of hsa‐miR‐103a and hsa‐miR‐1827 and hsa‐miR‐137 as new regulators of Wnt signaling pathway and their relation to colorectal carcinoma. Issue 7 (7th March 2018) - Fasihi, Ali; M. Soltani, Bahram; Atashi, Amir; Nasiri, Shirzad
Abstract: Wnt signaling is hyper‐activated in most of human cancers including colorectal carcinoma (CRC). Therefore, the introduction of new regulators for Wnt pathway possesses promising diagnostic and therapeutic applications in cancer medicine. Bioinformatics analysis introduced hsa‐miR‐103a, hsa‐miR‐1827, and hsa‐miR‐137 as potential regulators of Wnt signaling pathway. Here, we intended to examine the effect of these human miRNAs on Wnt signaling pathway components, on the cell cycle progression in CRC originated cell lines and their expression in CRC tissues. RT‐qPCR results indicated upregulation of hsa‐miR‐103a, hsa‐miR‐1827, and downregulation of hsa‐miR‐137 in CRC tissues. Overexpression of hsa‐miR‐103a and hsa‐miR‐1827 in SW480 cells resulted in elevated Wnt activity, detected by both Top/Flash assay and RT‐qPCR analysis. Inhibition of Wnt signaling by using PNU‐74654 or IWP‐2 small molecules suggested that these miRNAs exerts their effect at the β‐catenin degradation complex level. Then, RT‐qPCR, dual luciferase assay, and western blotting analysis indicated that APC and APC2 transcripts were targeted by hsa‐miR‐103a, hsa‐miR‐1827 while, Wnt3a and β ‐ catenin genes were upregulated. However, hsa‐miR‐137 downregulated Wnt3a and β ‐ catenin genes. Further, hsa‐miR‐103a and hsa‐miR‐1827 overexpression resulted in cell cycle progression and reduced apoptotic rate in SW480 cells, unlike hsa‐miR‐137 overexpression which resulted in cell cycle suppression, detected by flowcytometry and Anexin analysis. Overall, our data introduced hsa‐miR‐103a, hsa‐miR‐1827 as onco‐miRNAs and hsa‐miR‐137 as tumor suppressor which exert their effect through regulation of Wnt signaling pathway in CRC and introduced them as potential target for therapy. Abstract : Using Top/Flash assay, RT‐qPCR analysis, Western blotting, and dual luciferace assay followed by cell cycle and apoptosis assay, we intended to examine the effect of three selected miRNAs on Wnt signaling pathway components, to introduction of new regulators for this pathway in colorectal cancer.